Exploring the Impact of Adversity Quotient on Students' Mathematics Achievement in Junior High School - Mustafa, Sriyanti; Sulvianti, Sulvianti; Rasmi, Rasmi; Yunus, A. Andriani (Jurnal Pendidikan MIPA, 2025)
Adversity Quotient (AQ) is an individual’s ability to face and overcome obstacles and has been found to be an important non-cognitive factor in student learning outcomes, especially in mathematics, a subject often perceived as difficult and stressful. This study aimed to examine the effect of AQ on grade VIII students’ mathematics learning achievement at SMP Negeri 2 Parepare. A quantitative approach was used with 36 students selected through cluster random sampling. Data was collected using a validated AQ questionnaire based on Stoltz’s CO2RE model, consisting of Control, Origin and Ownership, Reach, and Endurance, as well as students’ mathematics learning achievement scores. Descriptive analysis showed that students generally had moderate AQ, with the highest dimension score in endurance, which means optimism and persistence, while the control dimension was the weakest. This means that although students are motivated to face challenges, they still struggle to manage their responses to learning pressure. The study applied Spearman’s rho correlation analysis. This finding implies that non-cognitive skills such as AQ in mathematics education will improve their academic outcomes. A high AQ in students will tend to be able to overcome difficulties and problems well it has a good impact on their learning achievement. This study has limitations. Small sample size (N=36) limits generalizability beyond a specific school context. This study only focused on AQ as an internal factor without considering external factors such as socioeconomic status, parental support, or classroom atmosphere. Future research will expand the sample and include additional variables to understand the multifactorial nature of academic success.      Keywords: adversity quotient; achievement; learning; mathematics.